2007
DOI: 10.1007/s10765-007-0257-0
|View full text |Cite
|
Sign up to set email alerts
|

Density, Surface Tension, and Viscosity of CMSX-4® Superalloy

Abstract: The surface tension, density, and viscosity of the Ni-based superalloy CMSX-4 have been determined in the temperature ranges of 1,650-1,850 K, 1,650-1,950 K, and 1,623-1,800 K, respectively. Each property has been measured in parallel by different techniques at different participating laboratories, and the results are compared with the aim to improve the reliability of data and to identify recommended values. The following relationships have been proposed: density-ρ (T ) [kg·m −3 ] = 7,876−1.23(T −1, 654 K); s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…Among the datasets shown in Fig. 8, the surface tension data of CMSX-4 [22] result lower than expected with respect to the Al content in the entire temperature range of measure. However, the surface tension of CMSX-4 as a function of temperature has been widely discussed in the literature [16,21,23,24], showing that its surface tension values exhibit a large scatter.…”
Section: Surface Tensionmentioning
confidence: 68%
See 2 more Smart Citations
“…Among the datasets shown in Fig. 8, the surface tension data of CMSX-4 [22] result lower than expected with respect to the Al content in the entire temperature range of measure. However, the surface tension of CMSX-4 as a function of temperature has been widely discussed in the literature [16,21,23,24], showing that its surface tension values exhibit a large scatter.…”
Section: Surface Tensionmentioning
confidence: 68%
“…8. The new surface tension data as a function of temperature together with the experimental data of the Ni-based superalloys previously measured under the same experimental conditions [12,22] are shown in Fig. 8.…”
Section: Surface Tensionmentioning
confidence: 88%
See 1 more Smart Citation
“…In the same work, the surface tension of CMSX-4 at T liq was obtained as r(T liq ) = 1.81 Nm À1 in good agreement with our previously reported value of r(T liq ) = 1.79 N m À1 . For CMSX-4, Ricci et al [46] reported a value r(T liq ) = 1.77 N m À1 and a temperature coefficient of -5. 6 9 10 À4 N m À1 K À1 measured by the pinned drop method.…”
Section: A Surface Tensionmentioning
confidence: 99%
“…The most extensively used for liquid metals is the oscillating-cup method, as recently reported for Cu-Sn alloys [6], Ni-based alloys [7], and In-Se-Tl alloys [8]. Details of this method and working equations can be found elsewhere [9] and therefore will be only briefly presented here.…”
Section: Introductionmentioning
confidence: 99%